Starch-based biodegradable plastic and preparation method thereof

Through the cross-linking reaction of high amylose and the addition of natural plasticizers and other agents, the problem of existing degradable plastics being easily hydrolyzed in humid environments is solved, and the rapid degradation and performance improvement of starch-based biodegradable plastics are achieved.

CN119505378AInactive Publication Date: 2025-02-25YANGZHOU POLYTECHNIC INST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411670488.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing biodegradable plastics are prone to hydrolysis in humid environments, have reduced mechanical properties, and are degraded slowly in natural environments, resulting in long-term pollution.

Method used

High amylose as the main raw material, prepared by solution method and cross-linking reaction in a high temperature and high pressure environment to form a three-dimensional network structure, enhance mechanical strength and moisture resistance, and add natural plasticizers, chemical cross-linking agents, antioxidants and Antibacterial agents to improve performance.

Benefits of technology

It realizes the rapid degradation of starch-based biodegradable plastics in the natural environment, reduces long-term pollution, and improves the mechanical strength, moisture resistance and antibacterial properties of the material, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005145712930000141
    Figure BDA0005145712930000141
  • Figure BDA0005145712930000151
    Figure BDA0005145712930000151
Patent Text Reader

Abstract

The invention relates to the technical field of degradable plastics, and particularly discloses a starch-based biodegradable plastic and a preparation method thereof.The preparation method includes the steps that high-amylose starch (such as corn, potatoes and cassava) is selected as a raw material and cleaned, dried and ground to obtain starch powder, a natural plasticizer (such as glycerin) is added to improve the flexibility, and the starch-based biodegradable plastic is obtained; a chemical cross-linking agent (such as glutaraldehyde) is used for enhancing the strength and the heat stability, an antioxidant (such as vitamin E) and an antibacterial agent (such as tea polyphenol) are used as additives, and the mass ratio of the antioxidant to the antibacterial agent is (0.6-0.85): (0.05-0.2): (0.005-0.03): (0.001-0.01): (0.001-0.005). The starch-based bioplastic prepared by the invention has good degradation performance and adjustability, is particularly suitable for the fields of disposable packaging, agricultural films, medical materials and the like, has a natural antibacterial function and ultraviolet protection capability, has huge application potential in the fields of medical treatment, food packaging and environmental protection, and has wide application prospects. The advantages of the starch-based plastic in agricultural application are also realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of degradable plastics, and in particular to a starch-based biodegradable plastic and a preparation method thereof. Background Art

[0002] Degradable plastics refer to plastics that can be decomposed into simple compounds under the action of microorganisms in the natural environment. Unlike traditional plastics, the main feature of degradable plastics is that they can be degraded relatively quickly after use, reducing long-term pollution to the environment, especially the harm of plastic waste to the ecosystem. With the improvement of environmental protection awareness and the increasing concern about plastic pollution, the research and development and application prospects of degradable plastics are promising.

[0003] Starch is a polysaccharide composed of glucose molecules connected by glycosidic bonds. It is one of the ways that plants widely store energy. It is the main energy storage substance in plant cells and is usually stored in roots, stems, leaves and fruits. It is especially abundant in plants such as potatoes, corn, wheat and rice. Starch-based plastic is a degradable plastic made by using starch as the main raw material. Starch is a natural biodegradable material and has great potential as a plastic substitute. Especially in the context of environmental protection and sustainable development, starch-based plastic is regarded as a green alternative material to solve the problem of plastic pollution.

[0004] Existing degradable plastics, such as polylactic acid (PLA) and polyhydroxyalkanoate (PHA), rely on agricultural raw materials (such as corn, sugar cane, etc.), which will lead to competition for land resources and sustainability of agricultural production methods. Some common degradable plastics (such as PLA) are easily hydrolyzed or degraded in a humid environment, resulting in reduced mechanical properties, especially in high humidity or high temperature environments. Existing degradable plastics (such as PLA) still have certain limitations in terms of enhanced performance and functionality. For example, PLA has poor performance in terms of waterproofness, antibacterial properties, etc., which limits its performance in specific applications (such as agricultural mulch, medical packaging). Although many degradable plastics (such as PLA) have certain biodegradability, their degradation process often needs to be carried out in a specific industrial composting environment, and the degradation rate is slow in the natural environment, which causes certain plastic pollution in the natural environment. Therefore, the present invention proposes a starch-based biodegradable plastic and a preparation method thereof to solve the problems mentioned in the above background technology. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a starch-based biodegradable plastic and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A starch-based biodegradable plastic and a preparation method thereof, specifically comprising the following steps:

[0008] Step 1. Raw material selection and pretreatment

[0009] Select high-amylose starch (such as corn, potato, cassava, etc.) as the main raw material. High-amylose starch has strong crystallinity and can provide better physical properties. The starch is washed, dried and ground to remove impurities and moisture to obtain starch powder suitable for subsequent processing. The raw material pretreatment is to remove impurities by washing with water, and use low-temperature drying (such as air drying equipment or freeze drying) to avoid thermal degradation of starch. The drying time is controlled within 4-6 hours until the moisture content of the starch drops below 10%, and the starch is ground to between 100-300 μm;

[0010] Preferably, natural plasticizers (such as glycerol, lactic acid or citric acid) are selected to improve the flexibility and processability of starch-based plastics, chemical cross-linking agents (such as glutaraldehyde, isocyanate, epoxy resin, etc.) are selected to enhance the strength, moisture resistance and thermal stability of starch-based plastics, and natural antioxidants (such as vitamin E, citric acid) and antibacterial agents (such as tea polyphenols, silver ions, etc.) are selected as additives to improve the stability and antibacterial properties of starch-based plastics.

[0011] Preferably, the mass ratio of the high-amylose starch, natural plasticizer, chemical cross-linking agent, natural antioxidant and antibacterial agent is (0.6-0.85):(0.05-0.2):(0.005-0.03):(0.001-0.01):(0.001-0.005).

[0012] Step 2. Preparation of starch solution by solution method

[0013] The starch in step 1 is mixed with an appropriate amount of water or an environmentally friendly solvent (such as lactic acid, glycerol, acetone, etc.), and heated (80-90° C.) and stirred in an electric heating container to dissolve the starch molecules and form a uniform starch solution. The amount of water added is controlled to be 50%-70% (starch / water mass ratio), and heated and stirred at 80-90° C. for 30-60 minutes to ensure that the starch is completely dissolved. After the temperature is stable, a plasticizer and a cross-linking agent are added, and an antioxidant and an antibacterial agent are added at a temperature of 60-80° C.;

[0014] Preferably, the natural plasticizer and cross-linking agent selected in step 1 are added to the starch solution and stirred evenly, and the antioxidant and antibacterial agent selected in step 1 are added and stirred evenly to improve the stability and antibacterial function of the plastic. During the stirring process, a magnetic stirrer or a mechanical stirrer is required to ensure that the solution is uniform and prevent the generation of foam or bubbles, because the foam will affect the subsequent spinning and molding process. If natural plasticizers are used, they may form strong hydrogen bonds with starch, and special attention should be paid to ensure that they are evenly dispersed during stirring.

[0015] Step 3. Solution spinning and other processing

[0016] The starch solution obtained in step 2 is placed in a high-pressure reactor to promote the cross-linking reaction in a high-temperature and high-pressure environment. The cross-linking reaction time is 30-60 minutes, so that the starch molecules form a three-dimensional network structure, thereby enhancing its mechanical strength, moisture resistance and thermal stability.

[0017] Preferably, the starch solution obtained in step 2 is extruded through a spinning device (e.g., a fine-mouth nozzle) and quickly dried in temperature-controlled air. The drying temperature is controlled between 100-120°C to ensure that the water or solvent in the solution can evaporate quickly to avoid the formation of impurities or affecting the mechanical properties of the final product, forming a starch-based film or fiber material. The solution is extruded using a spinning device with a fine-mouth nozzle, the spinning aperture is 0.1-0.3mm, and the air temperature is maintained at 50-60°C to ensure rapid drying without warping or unevenness.

[0018] Step 4. Extrusion and post-processing

[0019] The starch material obtained in step 3 is formed by an extruder, and the starch mixture is melt-extruded at a controlled temperature (120-160° C.) by a twin-screw extruder. During this process, the cross-linked structure between starch molecules can be further strengthened, and the shape and performance of the plastic material are also improved. The melt after extrusion is shaped by a cooling mold to form products in different forms such as films, granules, pipes or sheets;

[0020] Preferably, natural plant extracts are used, and an antibacterial coating (such as tea polyphenols or silver ions) is sprayed on the plastic surface to enhance its antibacterial properties and UV resistance. The plastic surface is subjected to corona or plasma treatment to improve its surface wettability and adhesion, and increase its adhesion with other materials. The antibacterial coating is applied to the plastic surface by spraying or dipping. The corona treatment is carried out in the range of -5-0°C for 30-60s. The pressure of the plasma treatment is controlled at 50-200Pa. The corona treatment process is controlled at a low voltage (5-20kV), and the plastic surface is treated by a short high-frequency electric field.

[0021] Step 5. Product performance testing

[0022] The products obtained in step 4 are sampled and tested, including tensile strength, elongation at break, impact strength, etc., to ensure that the materials meet the requirements of practical applications. The mechanical properties of the products are evaluated through tensile and impact tests. Tensile strength and elongation at break are important indicators for evaluating the toughness and flexibility of materials. The tensile test usually adopts the ASTM D882 standard, and the impact strength is used to evaluate the impact resistance of the material, usually adopting the ASTM D256 standard;

[0023] Preferably, simulate the soil or marine environment, observe the degradation time of the material, ensure that it degrades within an appropriate time, and avoid premature or slow degradation. The degradation time depends on the source of the starch, the degree of cross-linking and the external environment. Degradability is usually evaluated by mass loss or morphological change. The degradation time should be controlled between 6 months and 2 years. The specific time can be adjusted by changing the cross-linking agent concentration, plasticizer type, etc.

[0024] A starch-based biodegradable plastic is prepared by the above-mentioned preparation method.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The starch-based biodegradable plastic of the present invention uses natural renewable starch as the main raw material, avoiding the dependence of traditional plastics on petroleum resources and having a lower carbon footprint. Unlike petroleum-based plastics, starch-based plastics have good biodegradability and can be quickly degraded in the natural environment, reducing long-term pollution, and meeting the growing global demand for environmentally friendly materials;

[0027] 2. The physical properties of starch-based plastics are significantly improved by appropriately selecting natural plasticizers, chemical crosslinking agents, and antioxidant and antibacterial additives. These materials can achieve high mechanical strength, moisture resistance, and thermal stability, solving the problem of easy hydrolysis of traditional degradable plastics (such as PLA) in a humid environment. In addition, the three-dimensional network structure formed by the crosslinking reaction enhances the mechanical properties and impact resistance of the material, making it more suitable for a variety of application scenarios.

[0028] 3. Compared with traditional plastics, the production process of the starch-based plastic of the present invention adopts low-temperature, environmentally friendly solvents, avoids the use of harmful solvents, and reduces harm to the environment and health. At the same time, starch as a raw material has low cost and a wide source, and has good economy and production sustainability. Especially in areas rich in agricultural by-products, the production cost and resource acquisition advantages are more obvious.

[0029] In summary, the starch-based bioplastic prepared in this scheme has good degradation performance and adjustability, and is particularly suitable for disposable packaging, agricultural films, medical materials and other fields. Its natural antibacterial function and UV protection ability make it have great application potential in the fields of medical treatment, food packaging and environmental protection. At the same time, the advantages of starch-based plastics in agricultural applications have better environmental protection, adjustable functionality, lower cost and wider application space. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0031] Embodiment 1

[0032] A method for preparing a starch-based biodegradable plastic comprises the following steps:

[0033] Step 1. Raw material selection and pretreatment

[0034] High-amylose corn is selected as the main raw material. High-amylose corn has strong crystallinity and can provide good physical properties. The starch is washed, dried and ground to remove impurities and moisture to obtain starch powder suitable for subsequent processing. The raw material pretreatment is to remove impurities by washing with water, and low-temperature drying is performed using air drying equipment to avoid thermal degradation of starch. The drying time is controlled within 4 hours until the moisture content of the starch drops below 10%, and the starch is ground to between 100 μm;

[0035] Furthermore, glycerol is selected as a natural plasticizer to improve the flexibility and processability of starch-based plastics, glutaraldehyde is selected as a chemical cross-linking agent to enhance the strength, moisture resistance and thermal stability of starch-based plastics, and natural antioxidant vitamin E and antibacterial agents tea polyphenols and silver ions are selected as additives to improve the stability and antibacterial properties of starch-based plastics.

[0036] Preferably, the mass ratio of the high-amylose starch, natural plasticizer, chemical cross-linking agent, natural antioxidant and antibacterial agent is 0.6:0.05:0.006:0.005:0.001.

[0037] Step 2. Preparation of starch solution by solution method

[0038] The starch in step 1 is mixed with an appropriate amount of water or an environmentally friendly solvent (such as lactic acid, glycerol, acetone, etc.), and heated to 80° C. and stirred in an electric heating container to dissolve the starch molecules to form a uniform starch solution. The amount of water added is controlled to 50% (starch / water mass ratio), and heated and stirred at 80° C. for 40 minutes to ensure that the starch is completely dissolved. After the temperature is stable, a plasticizer and a cross-linking agent are added, and an antioxidant and an antibacterial agent are added at a temperature of 60° C.;

[0039] Furthermore, the natural plasticizer and cross-linking agent selected in step 1 are added to the starch solution and stirred evenly, and the antioxidant and antibacterial agent selected in step 1 are added and stirred evenly to improve the stability and antibacterial function of the plastic. During the stirring process, a magnetic stirrer or a mechanical stirrer is required to ensure that the solution is uniform and to prevent the generation of foam or bubbles, because the foam will affect the subsequent spinning and molding process. If natural plasticizers are used, they may form strong hydrogen bonds with starch, and special attention should be paid to ensure that they are evenly dispersed during stirring.

[0040] Step 3. Solution spinning and other processing

[0041] The starch solution obtained in step 2 is placed in a high-pressure reactor to promote the cross-linking reaction in a high-temperature and high-pressure environment. The cross-linking reaction time is 40 minutes, so that the starch molecules form a three-dimensional network structure, thereby enhancing its mechanical strength, moisture resistance and thermal stability.

[0042] Furthermore, the starch solution obtained in step 2 is extruded through a fine-mouth nozzle of a spinning device and quickly dried in temperature-controlled air. The drying temperature is controlled at 100°C to ensure that the water or solvent in the solution can evaporate quickly to avoid the formation of impurities or affecting the mechanical properties of the final product, so as to form a starch-based film or fiber material. The solution is extruded using a spinning device with a fine-mouth nozzle, the spinning aperture is 0.1 mm, and the air temperature is maintained at 50°C to ensure rapid drying without warping or unevenness.

[0043] Step 4. Extrusion and post-processing

[0044] The starch material obtained in step 3 is formed by an extruder, and the starch mixture is melt-extruded at a controlled temperature of 120° C. by a twin-screw extruder. During this process, the cross-linked structure between starch molecules can be further strengthened, and the shape and performance of the plastic material are also improved. The melt after extrusion is shaped by a cooling mold to form products in different forms such as films, granules, tubes or sheets;

[0045] Furthermore, using natural plant extracts, antibacterial coating tea polyphenols are sprayed on the plastic surface to enhance its antibacterial properties and UV resistance, and the plastic surface is treated with corona or plasma to improve its surface wettability and adhesion, and increase its adhesion with other materials. The antibacterial coating is applied to the plastic surface by spraying or dipping, and the corona treatment is carried out at -5°C for 30s. The pressure of the plasma treatment is controlled at 100Pa, the corona treatment process is controlled at a low voltage of 5kV, and the plastic surface is treated with a short high-frequency electric field.

[0046] Step 5. Product performance testing

[0047] The products obtained in step 4 are sampled and tested, including tensile strength, elongation at break, impact strength, etc., to ensure that the materials meet the requirements of practical applications. The mechanical properties of the products are evaluated through tensile and impact tests. Tensile strength and elongation at break are important indicators for evaluating the toughness and flexibility of materials. The tensile test usually adopts the ASTM D882 standard, and the impact strength is used to evaluate the impact resistance of the material, usually adopting the ASTM D256 standard;

[0048] Furthermore, the soil or marine environment is simulated, and the degradation time of the material is observed to ensure that it degrades within an appropriate time to avoid premature or slow degradation. The degradation time depends on the source of the starch, the degree of cross-linking and the external environment. Degradability is usually evaluated by mass loss or morphological changes. The degradation time should be controlled between 6 months and 2 years. The specific time can be adjusted by changing the cross-linker concentration, plasticizer type, etc.

[0049] Embodiment 2

[0050] A method for preparing a starch-based biodegradable plastic comprises the following steps:

[0051] Step 1. Raw material selection and pretreatment

[0052] Select high-amylose potato as the main raw material. High-amylose starch has strong crystallinity and can provide better physical properties. The starch is washed, dried and ground to remove impurities and moisture to obtain starch powder suitable for subsequent processing. The raw material pretreatment is to remove impurities by washing, freeze drying is used to avoid thermal degradation of starch, and the drying time is controlled within 5 hours until the moisture content of the starch drops below 10%, and the starch is ground to between 200 μm;

[0053] Furthermore, lactic acid is selected as a natural plasticizer to improve the flexibility and processability of starch-based plastics, isocyanate is selected as a chemical cross-linking agent to enhance the strength, moisture resistance and thermal stability of starch-based plastics, and natural antioxidant citric acid and antibacterial agent silver ions are selected as additives to improve the stability and antibacterial properties of starch-based plastics.

[0054] Preferably, the mass ratio of the high-amylose starch, natural plasticizer, chemical cross-linking agent, natural antioxidant and antibacterial agent is 0.7:0.1:0.02:0.006:0.002.

[0055] Step 2. Preparation of starch solution by solution method

[0056] The starch in step 1 is mixed with an appropriate amount of water or environmentally friendly solvent glycerin, and heated to 85° C. and stirred in an electric heating container to dissolve the starch molecules to form a uniform starch solution. The amount of water added is controlled to 60% (starch / water mass ratio), and heated and stirred at 85° C. for 40 minutes to ensure that the starch is completely dissolved. After the temperature is stable, a plasticizer and a cross-linking agent are added, and an antioxidant and an antibacterial agent are added at a temperature of 70° C.;

[0057] Furthermore, the natural plasticizer and cross-linking agent selected in step 1 are added to the starch solution and stirred evenly, and the antioxidant and antibacterial agent selected in step 1 are added and stirred evenly to improve the stability and antibacterial function of the plastic. During the stirring process, a magnetic stirrer or a mechanical stirrer is required to ensure that the solution is uniform and to prevent the generation of foam or bubbles, because the foam will affect the subsequent spinning and molding process. If natural plasticizers are used, they may form strong hydrogen bonds with starch, and special attention should be paid to ensure that they are evenly dispersed during stirring.

[0058] Step 3. Solution spinning and other processing

[0059] The starch solution obtained in step 2 is placed in a high-pressure reactor to promote the cross-linking reaction in a high-temperature and high-pressure environment. The cross-linking reaction time is 50 minutes, so that the starch molecules form a three-dimensional network structure, thereby enhancing its mechanical strength, moisture resistance and thermal stability.

[0060] Furthermore, the starch solution obtained in step 2 is extruded through a spinning device with a fine nozzle, and quickly dried in temperature-controlled air. The drying temperature is controlled at 110°C to ensure that the water or solvent in the solution can evaporate quickly to avoid the formation of impurities or affecting the mechanical properties of the final product, thereby forming a starch-based film or fiber material. The solution is extruded using a spinning device with a fine nozzle, the spinning aperture is 0.2 mm, and the air temperature is maintained at 55°C to ensure rapid drying without warping or unevenness.

[0061] Step 4. Extrusion and post-processing

[0062] The starch material obtained in step 3 is formed by an extruder, and the starch mixture is melt-extruded at a controlled temperature of 140° C. by a twin-screw extruder. During this process, the cross-linked structure between starch molecules can be further strengthened, and the shape and performance of the plastic material are also improved. The melt after extrusion is shaped by a cooling mold to form products in different forms such as films, granules, tubes or sheets;

[0063] Furthermore, using natural plant extracts, antibacterial coating silver ions are sprayed on the plastic surface to enhance its antibacterial properties and UV resistance, and the plastic surface is treated with corona or plasma to improve its surface wettability and adhesion, and increase its adhesion with other materials. The antibacterial coating is applied to the plastic surface by spraying or dipping. The corona treatment is carried out at a temperature of -2°C for 40 seconds. The pressure of the plasma treatment is controlled at 100Pa. The corona treatment process is controlled at a low voltage of 15kV, and the plastic surface is treated with a short high-frequency electric field.

[0064] Step 5. Product performance testing

[0065] The products obtained in step 4 are sampled and tested, including tensile strength, elongation at break, impact strength, etc., to ensure that the materials meet the requirements of practical applications. The mechanical properties of the products are evaluated through tensile and impact tests. Tensile strength and elongation at break are important indicators for evaluating the toughness and flexibility of materials. The tensile test usually adopts the ASTM D882 standard, and the impact strength is used to evaluate the impact resistance of the material, usually adopting the ASTM D256 standard;

[0066] Furthermore, the soil or marine environment is simulated, and the degradation time of the material is observed to ensure that it degrades within an appropriate time to avoid premature or slow degradation. The degradation time depends on the source of the starch, the degree of cross-linking and the external environment. Degradability is usually evaluated by mass loss or morphological changes. The degradation time should be controlled between 6 months and 2 years. The specific time can be adjusted by changing the cross-linker concentration, plasticizer type, etc.

[0067] Embodiment 3

[0068] A method for preparing a starch-based biodegradable plastic comprises the following steps:

[0069] Step 1. Raw material selection and pretreatment

[0070] High-amylose cassava is selected as the main raw material. High-amylose starch has strong crystallinity and can provide better physical properties. The starch is washed, dried and ground to remove impurities and moisture to obtain starch powder suitable for subsequent processing. The raw material pretreatment is to remove impurities by washing, freeze drying is used to avoid thermal degradation of starch, and the drying time is controlled within 6 hours until the moisture content of the starch drops below 10%, and the starch is ground to between 300 μm;

[0071] Furthermore, citric acid is selected as a natural plasticizer to improve the flexibility and processability of starch-based plastics, epoxy resin is selected as a chemical cross-linking agent to enhance the strength, moisture resistance and thermal stability of starch-based plastics, and natural antioxidant citric acid and antibacterial agent silver ions are selected as additives to improve the stability and antibacterial properties of starch-based plastics.

[0072] Preferably, the mass ratio of the high-amylose starch, natural plasticizer, chemical cross-linking agent, natural antioxidant and antibacterial agent is 0.85:0.2:0.03:0.01:0.005.

[0073] Step 2. Preparation of starch solution by solution method

[0074] The starch in step 1 is mixed with an appropriate amount of water or an environmentally friendly solvent such as acetone, and heated to 90° C. and stirred in an electric heating container to dissolve the starch molecules to form a uniform starch solution. The amount of water added is controlled to 70% (starch / water mass ratio), and heated and stirred at 90° C. for 60 minutes to ensure that the starch is completely dissolved. After the temperature is stable, a plasticizer and a cross-linking agent are added, and an antioxidant and an antibacterial agent are added at a temperature of 80° C.;

[0075] Furthermore, the natural plasticizer and cross-linking agent selected in step 1 are added to the starch solution and stirred evenly, and the antioxidant and antibacterial agent selected in step 1 are added and stirred evenly to improve the stability and antibacterial function of the plastic. During the stirring process, a magnetic stirrer or a mechanical stirrer is required to ensure that the solution is uniform and to prevent the generation of foam or bubbles, because the foam will affect the subsequent spinning and molding process. If natural plasticizers are used, they may form strong hydrogen bonds with starch, and special attention should be paid to ensure that they are evenly dispersed during stirring.

[0076] Step 3. Solution spinning and other processing

[0077] The starch solution obtained in step 2 is placed in a high-pressure reactor to promote the cross-linking reaction in a high-temperature and high-pressure environment. The cross-linking reaction time is 50 minutes, so that the starch molecules form a three-dimensional network structure, thereby enhancing its mechanical strength, moisture resistance and thermal stability.

[0078] Furthermore, the starch solution obtained in step 2 is extruded through a fine-mouth nozzle of a spinning device and quickly dried in temperature-controlled air. The drying temperature is controlled at 120°C to ensure that the water or solvent in the solution can evaporate quickly to avoid the formation of impurities or affecting the mechanical properties of the final product, thereby forming a starch-based film or fiber material. The solution is extruded using a fine-mouth nozzle spinning device with a spinning aperture of 0.3 mm and the air temperature is maintained at 60°C to ensure rapid drying without warping or unevenness.

[0079] Step 4. Extrusion and post-processing

[0080] The starch material obtained in step 3 is formed by an extruder, and the starch mixture is melt-extruded at a controlled temperature of 160° C. by a twin-screw extruder. During this process, the cross-linked structure between starch molecules can be further strengthened, and the shape and performance of the plastic material are also improved. The melt after extrusion is shaped by a cooling mold to form products in different forms such as films, granules, tubes or sheets;

[0081] Furthermore, using natural plant extracts, antibacterial coating silver ions are sprayed on the plastic surface to enhance its antibacterial properties and UV resistance, and the plastic surface is treated with corona or plasma to improve its surface wettability and adhesion, and increase adhesion with other materials. The antibacterial coating is applied to the plastic surface by spraying or dipping, and the corona treatment is carried out at 0°C for 60s. The pressure of the plasma treatment is controlled at 200Pa, the corona treatment process is controlled at a low voltage of 20kV, and the plastic surface is treated with a short high-frequency electric field.

[0082] Step 5. Product performance testing

[0083] The products obtained in step 4 are sampled and tested, including tensile strength, elongation at break, impact strength, etc., to ensure that the materials meet the requirements of practical applications. The mechanical properties of the products are evaluated through tensile and impact tests. Tensile strength and elongation at break are important indicators for evaluating the toughness and flexibility of materials. The tensile test usually adopts the ASTM D882 standard, and the impact strength is used to evaluate the impact resistance of the material, usually adopting the ASTM D256 standard;

[0084] Furthermore, the soil or marine environment is simulated, and the degradation time of the material is observed to ensure that it degrades within an appropriate time to avoid premature or slow degradation. The degradation time depends on the source of the starch, the degree of cross-linking and the external environment. Degradability is usually evaluated by mass loss or morphological changes. The degradation time should be controlled between 6 months and 2 years. The specific time can be adjusted by changing the cross-linker concentration, plasticizer type, etc.

[0085] Table 1: Performance of the above three embodiments in material performance testing

[0086]

[0087]

[0088] A common degradable plastic polylactic acid in the field was selected as a control example, and compared with the above examples 1, 2, and 3 in terms of tensile strength, elongation at break, impact strength, and degradation time, and its outstanding performance compared with traditional plastics was examined in various aspects;

[0089] Tensile strength refers to the maximum stress that a material can withstand during stretching, reflecting its ability to resist stretching. A higher tensile strength (e.g., ≥20 MPa) generally indicates that the material is relatively strong and suitable for applications with higher load-bearing requirements. The tensile strengths of the above-mentioned embodiments are all greater than 20 MPa.

[0090] Elongation at break refers to the maximum elongation of a material before breaking (as a percentage of its initial length), which reflects the flexibility of the material. A higher elongation at break (e.g., ≥50%) generally indicates that the material has better flexibility and ductility. The elongation at break of the above-mentioned multiple embodiments is kept at a high level.

[0091] Impact strength refers to the ability of a material to withstand impact in a short period of time. 2 ) means that the material has good impact resistance and can withstand instantaneous loads. The impact strength of the above embodiments is much higher than the standard value;

[0092] Degradation time refers to the degradation cycle of a material in a specific environment (such as soil, ocean, compost, etc.). In a soil or compost environment, the degradation time of starch-based plastics should usually be completed within 3-6 months to avoid long-term environmental pollution. Degradation within 1 month means that the material is more environmentally friendly in the environment. In the above embodiments, the degradation time is about one month.

[0093] In summary, the starch-based biodegradable plastic obtained in this embodiment group under the present preparation method performs better than general traditional degradable plastics in terms of tensile strength, elongation at break, impact strength and degradation time, showing the advantages of the starch-based biodegradable plastic in structural strength and environmental protection.

[0094] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a starch-based biodegradable plastic, characterized in that: The specific steps include: Step 1. Raw material selection and pretreatment Select high-amylose starch (such as corn, potato, cassava) as the main raw material, wash, dry and grind the starch to remove impurities and moisture, and obtain starch powder suitable for subsequent processing; Select natural plasticizers (such as glycerol, lactic acid or citric acid) to improve the flexibility and processability of starch-based plastics, select chemical cross-linking agents (such as glutaraldehyde, isocyanate, epoxy resin, etc.) to enhance the strength, moisture resistance and thermal stability of starch-based plastics, and select natural antioxidants (such as vitamin E, citric acid) and antibacterial agents (such as tea polyphenols, silver ions, etc.) as additives; The mass ratio of the high-amylose starch, natural plasticizer, chemical cross-linking agent, natural antioxidant and antibacterial agent is (0.6-0.85): (0.05-0.2): (0.005-0.03): (0.001-0.01): (0.001-0.005). Step 2. Preparation of starch solution by solution method Mix the starch in step 1 with water or an environmentally friendly solvent (such as lactic acid, glycerol, acetone, etc.), heat it in an electric heating container (80-90° C.) and stir it to dissolve the starch molecules and form a uniform starch solution; Add the natural plasticizer and cross-linking agent selected in step 1 to the starch solution, stir evenly, add the antioxidant and antibacterial agent selected in step 1, and stir evenly. Step 3. Solution spinning and other processing The starch solution obtained in step 2 is placed in a high-pressure reactor, and the cross-linking reaction is promoted by a high-temperature and high-pressure environment under the conditions of controlling the temperature (120-150° C.) and the pressure (0.5-1.5 MPa). The cross-linking reaction time is 30-60 minutes, so that the starch molecules form a three-dimensional network structure; The starch solution obtained in step 2 is extruded through a spinning device and rapidly dried in temperature-controlled air to form a starch-based film or fiber material. Step 4. Extrusion and post-processing The starch material obtained in step 3 is formed by an extruder, and the starch mixture is melt-extruded at a controlled temperature (120-160° C.) by a twin-screw extruder, and the melt after extrusion is shaped by a cooling mold; Using natural plant extracts, antibacterial coatings (such as tea polyphenols or silver ions) are sprayed on the plastic surface, and the plastic surface is treated with corona or plasma. Step 5. Product performance testing The products obtained in step 4 are sampled and tested, including tensile strength, elongation at break, and impact strength, to ensure that the materials meet the requirements of practical applications; Simulate soil or marine environments and observe the degradation time of materials to ensure that they degrade within the appropriate time and avoid premature or slow degradation.

2. The method for preparing starch-based biodegradable plastic according to claim 1, characterized in that: In the step 1, the raw material is pretreated by washing to remove impurities, and low-temperature drying (such as air drying equipment or freeze drying) is used to avoid thermal degradation of starch. The drying time is controlled within 4-6 hours until the moisture content of the starch drops below 10%, and the starch is ground to between 100-300 μm.

3. The method for preparing starch-based biodegradable plastic according to claim 1, characterized in that: In the step 2, the amount of water added is controlled at 50%-70% (starch / water mass ratio), and the mixture is heated and stirred at 80-90° C. for 30-60 minutes to ensure that the starch is completely dissolved. After the temperature stabilizes, the plasticizer and cross-linking agent are added, and the antioxidant and antibacterial agent are added at a temperature of 60-80° C.

4. The method for preparing starch-based biodegradable plastic according to claim 1, characterized in that: The step 3 promotes the cross-linking reaction under the conditions of (120-150° C.) and pressure (0.5-1.5 MPa), and the solution is extruded using a spinning device with a fine nozzle, the spinning aperture is 0.1-0.3 mm, and the air temperature is maintained at 50-60° C. to ensure rapid drying without warping or unevenness.

5. The method for preparing starch-based biodegradable plastic according to claim 1, characterized in that: In step 4, the antibacterial coating is applied to the plastic surface by spraying or dipping, the corona treatment is performed in the range of -5-0°C for 30-60s, and the pressure of the plasma treatment is controlled at 50-200Pa.

6. The method for preparing starch-based biodegradable plastic according to claim 1, characterized in that: During the stirring process in step 2, a magnetic stirrer or a mechanical stirrer is required to ensure that the solution is uniform and to prevent the generation of foam or bubbles.

7. The method for preparing starch-based biodegradable plastic according to claim 1, characterized in that: In step 3, the temperature-controlled air is used for rapid drying, and the drying temperature is controlled between 100-120°C.

8. The method for preparing starch-based biodegradable plastic according to claim 1, characterized in that: In step 4, the corona treatment process is controlled to be carried out at a low voltage (5-20 kV), and the plastic surface is treated by a short high-frequency electric field.

9. A starch-based biodegradable plastic, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Cited By

  • Antibacterial degradable meal box material and preparation method thereof

    CN120758005A